1998
DOI: 10.1002/(sici)1099-1646(1998110)14:6<519::aid-rrr518>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation and recolonization of phytobenthos in a regulated desert river: Colorado River at Lees Ferry, Arizona, USA

Abstract: We tested the recolonization of the phytobenthic community in the tailwaters of Glen Canyon Dam following longand short-term experimentally induced desiccation. The response of Cladophora glomerata, Oscillatoria spp., miscellaneous phytobenthos species and periphyton was studied over 18 weeks using three treatments: (1) undisturbed control cobbles from the submerged zone; (2) cobbles desiccated and replaced into the submerged zone; and (3) cobbles desiccated and replaced into the varial zone. Periphyton densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This theoretical justification can explain the local replacement of Stigeoclonium amoenum by other species with higher relative abundances. A similar pattern was described by Benenati et al (1998) in a study of the recolonization of phytobenthos in a regulated desert stream after an experimental drought period. The authors showed that After the disturbance, the macroalgal community was greatly modified.…”
Section: Discussionsupporting
confidence: 81%
“…This theoretical justification can explain the local replacement of Stigeoclonium amoenum by other species with higher relative abundances. A similar pattern was described by Benenati et al (1998) in a study of the recolonization of phytobenthos in a regulated desert stream after an experimental drought period. The authors showed that After the disturbance, the macroalgal community was greatly modified.…”
Section: Discussionsupporting
confidence: 81%
“…Weakened parts of the algae filaments that are damaged due to desiccation are easily broken, causing loss of the damaged portions of the filaments and the viable parts (Usher & Blinn 1990). Benenati et al (1998) reported a pronounced decline of Cladophora filaments and its periphyton epiphytes as a consequence of the repeated episodes of exposure and desiccation. According to Lowe (1996) andDodds (1991), filamentous algae, such as oedogoniophyceans, continuously create new and complex areas through growth, increasing the area available for epiphytism.…”
Section: Discussionmentioning
confidence: 99%
“…Periphyton and other communities may respond in different manners to the onset, duration and cessation of a disturbance. Changes in hydrometric levels caused by dam operations should create periods of shortterm desiccation (10-15 hours), owing to a diel tide associated with daily electricity demand (Benenati et al 1998), and may strongly influence periphyton communities (Benenati et al 1998;Bergey et al 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually fish populations and communities change in conjunction with decreases in productivity Ney 1989, Pefiaz et al 1999). For example, changes in seasonal flow patterns, dewatering of varial zones, loss of flushing flows, and temperature changes are known to play roles in altering the fish species composition and life history characteristics (Benenati et al 1998, Bain et al 1988, Binn et al 1995, McKinney et al 2001). …”
Section: Introductionmentioning
confidence: 99%